Mortality among uranium miners in North America and Europe: the Pooled Uranium Miners Analysis (PUMA). (24th November 2020) - Richardson, D B; Rage, E; Demers, P A; Do, M T; DeBono, N; Fenske, N; Deffner, V; Kreuzer, M; Samet, J; Wiggins, C; Schubauer-Berigan, M K; Kelly-Reif, K; et al.
Abstract: Background: The Pooled Uranium Miners Analysis (PUMA) study draws together information from cohorts of uranium miners from Canada, the Czech Republic, France, Germany and the USA. Methods: Vital status and cause of death were ascertained and compared with expectations based upon national mortality rates by computing standardized mortality ratios (SMRs) overall and by categories of time since first hire, calendar period of first employment and duration of employment as a miner. Results: There were 51 787 deaths observed among 118 329 male miners [SMR = 1.05; 95% confidence interval (CI): 1.04, 1.06]. The SMR was elevated for all cancers ( n = 16 633, SMR = 1.23; 95% CI: 1.21, 1.25), due primarily to excess mortality from cancers of the lung ( n = 7756, SMR = 1.90; 95% CI: 1.86, 1.94), liver and gallbladder ( n = 549, SMR = 1.15; 95% CI: 1.06, 1.25), larynx ( n = 229, SMR = 1.10; 95% CI: 0.97, 1.26), stomach ( n = 1058, SMR = 1.08; 95% CI: 1.02, 1.15) and pleura ( n = 39, SMR = 1.06; 95% CI: 0.75, 1.44). Lung-cancer SMRs increased with duration of employment, decreased with calendar period and persisted with time since first hire. Among non-malignant causes, the SMR was elevated for external causes ( n = 3362, SMR = 1.41; 95% CI: 1.36, 1.46) and respiratory diseases ( n = 4508, SMR = 1.32; 95% CI: 1.28, 1.36), most notably silicosis ( n = 814, SMR = 13.56; 95% CI: 12.64, 14.52), but not chronic obstructive pulmonary disease ( n = 1729, SMR = 0.98; 95% CI: 0.93, 1.02). Conclusions: Whereas there are important obstacles to the ability to detect adverse effects of occupational exposures via SMR analyses, PUMA provides evidence of excess mortality among uranium miners due to a range of categories of cause of death. The persistent elevation of SMRs with time since first hire as a uranium miner underscores the importance of long-term follow-up of these workers.